Credit Characteristics and Business Performance: A Survey of Women owned Microenterprises in Tanzania - Salia, Paul J.; Mbwambo, Jonathan S. (Asian Business Review, 2014)
This article provides assessment of the effects of four credit characteristics including size, interest rate, repayment period and borrowing experience on business performance. The article makes use of survey data collected from 217 women microcredit clients from Arusha, Dar es Salaam and Mwanza regions in Tanzania. Bivariate correlation analysis was used to find out specific effect of each of those four credit characteristics on three business performance measures namely total sales revenue, net profit and business net worth. The combined effect of all four credit characteristics on business performance was estimated by a multiple linear regression model. The findings revealed that size of credit was positively correlated with total sales revenue and business net worth at significant level. Interest rate was negatively correlated with all three measures of business performance at significant level. It was also found out that repayment period was positively correlated with all three business performance indicators at significant level. Furthermore, the study established that borrowing experience was positively correlated with total sales revenue at significant level but not with other two indicators. The model accounted for 25% of sales revenue, 9% of net profit and 28% of business net worth.